Estrutura populacional e diversidade genética da raça árabe no Brasil - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Recognized as one of the oldest and most influential horse breeds, the Arabian horse has an undefined and, supposedly heterogeneous origin, from the study results of mitochondrial-DNA, which indicate that significant genetic diversity. Considering the context of the ecological challenges that species are submitted, such as competition, predation, disease and others, genetic diversity is crucial in adaptation and evolution. Evaluation within the population is necessary for the implementation of the screening program to establish a proper management of the genetic stock, being determined by the size of the base population, but also for mating strategies. Genetic analysis of a population may be brought to completion by using family or molecular information. In the present study, its purpose was to evaluate the Arabian horse genetic diversity in Brazil, through the genealogical information in the Stud Book Brazilian Arabian Horse. The data of 54,506 animals were used, whose consistency was assessed by their pedigrees Breed Mate Pedigree Software® program and population parameters determined by analysis with Poprep program. The average age of males and females in reproduction was respectively 9.8 and 9.0 years. The turnover of mares in breeding can be considered high (59.02%) and the average generation interval over time considered was 9.1 years. For the analysis of inbreeding 11 classes were defined with 5% intervals where 4.32% of the population corresponded to levels above 10%. The average F of inbreeding found for the population was 1.98%, considering the data ancestors since 1808, and 2.90%, considering the data from 1964, when the creation of the Brazilian Stud Book of Arabian horse. These results are lower than those found in populations of Arabian horses in Europe, observing large population genetic diversity and may be related to the large size of the population, the gene flow of a large number of animal imports and the absence of important genetic bottlenecks. However, the high proportion of inbred animals in the population and the increase in mean inbreeding in the past two decades, suggest selection of adjustments, in order to prevent loss of genetic diversity in the future.
Population structure and genetic diversity on arabian horse in Brazil
Keywords: Raça Árabe; Genealogia; Estrutura populacional; Arabian horse; Genealogy; CNPQ::CIENCIAS EXATAS E DA TERRA